Occupational burnout and influence of work environment factors among family physicians in Khorasan Razavi - M mahdizadeh; A vafaei; A Taghipour; H Esmaeily; SM Mahdizadeh; H Ebrahimipour (طب کار)
Background: Burnout is a syndrome that results of occupational stress, causing decreased work efficiency, increased absenteeism and health care costs, quality decline of medical services for patients and could lead to dissatisfaction them. The aim of present study was to identify burnout and influential environment factors on burnout among family physicians. Methods: In this cross-sectional study, 145 family physicians practicing in Khorasan Razavi were selected by systematic randomly method. Data were collected via questionnaires, personal informations, and Maslach burnout inventory (MBI), work environment indicators and self report. Results were analyzed using descriptive and analytical tests by SPSS software version 16 (P<0.05). Results: The mean age of participants was 32/57±4/87, 37/2 % (54 persons) were male and 62/8 % (91 persons) were women with a work experience median of 39 months in the healthy team. Depersonalization and personal accomplishment dimensions were in moderate level and emotional exhaustion was in the high level. Work environment indicators had significant inverse correlation with emotional exhaustion and depersonalization and significant positive correlation with personal accomplishment. Conclusion: The severity of burnout is associated with work environment factors among family physician, and we could assist reduce their burnout via positive change in different domains of work environment.